Comparative Genomic Analysis Identifies a Campylobacter Clade Deficient in Selenium Metabolism. (10th May 2017) - Miller, William G.; Yee, Emma; Lopes, Bruno S.; Chapman, Mary H.; Huynh, Steven; Bono, James L.; Parker, Craig T.; Strachan, Norval J.C.; Forbes, Ken J.
Abstract: The nonthermotolerant Campylobacter species C. fetus, C. hyointestinalis, C. iguaniorum, and C. lanienae form a distinct phylogenetic cluster within the genus. These species are primarily isolated from foraging (swine) or grazing (e.g., cattle, sheep) animals and cause sporadic and infrequent human illness. Previous typing studies identified three putative novel C. lanienae -related taxa, based on either MLST or atpA sequence data. To further characterize these putative novel taxa and the C. fetus group as a whole, 76 genomes were sequenced, either to completion or to draft level. These genomes represent 26 C. lanienae strains and 50 strains of the three novel taxa. C. fetus, C. hyointestinalis and C. iguaniorum genomes were previously sequenced to completion; therefore, a comparative genomic analysis across the entire C. fetus group was conducted (including average nucleotide identity analysis) that supports the initial identification of these three novel Campylobacter species. Furthermore, C. lanienae and the three putative novel species form a discrete clade within the C. fetus group, which we have termed the C. lanienae clade. This clade is distinguished from other members of the C. fetus group by a reduced genome size and distinct CRISPR/Cas systems. Moreover, there are two signature characteristics of the C. lanienae clade. C. lanienae clade genomes carry four to ten unlinked and similar, but nonidentical, flagellin genes. Additionally, all 76 C. lanienae clade genomes sequenced demonstrate a complete absence of genes related to selenium metabolism, including genes encoding the selenocysteine insertion machinery, selenoproteins, and the selenocysteinyl tRNA.